Assessment of tree mortality on the Estonian Network of Forest Research Plots/ Puude väljalangevuse hindamine metsa kasvukäigu püsiproovitükkidel - Sims Allan; Mändma Ruth; Laarmann Diana; Korjus Henn (Metsanduslikud Uurimused, 2014)
Assessment of tree mortality provides deeper understanding of forest structure and functioning. This enables evaluation of stand sustainability and provides information on stand productivity, diversity and health condition. Tree mortality can be assessed by spatiotemporal patterns as well as by studying the processes and causes of mortality. Tree mortality is caused by specific disturbance agents or by the complex effect of various disturbances. The purpose of this study is to examine tree mortality in Estonian forests, determine the causes of tree death, and estimate how different management regimes affect tree mortality and its causes. This study is based on 360 sample plots measured in 2003-2005 and re-measured in 2008-2010. The sample plots were divided into recently managed (RM, 146 plots) and low intensity/unmanaged (LU, 214 plots) plots based on forest management regime. In total, 53,990 trees were measured, of which 20,020 were located on RM and 33,970 on LU plots. The tree mortality for 5-year period was 3.4% on RM plots and 8.0% on LU plots. The main cause of tree mortality in RM stands was insect damage, which attributes to 29.8% of tree mortality, whereas in LU stands the main cause was tree competition, which attributes to 45.4% of tree mortality. The analysis of tree mortality indicated that an increase in relative tree diameter in both stand types contributes to an increase in mortality due to insect, wind or fungal damage and diseases. Opposite results were received with respect to competition - the smaller the tree relative diameter, the more probable it is that a tree will die because of competition with neighbouring trees. The analysis of game damage and other causes of tree mortality showed that these were not dependent on the relative diameter of trees. The analysis of the overall probability of tree mortality revealed that relatively smaller trees have a higher probability of mortality than larger trees.